Optimizing microwave-assisted extraction of phenolic compounds, in vitro antioxidant and anti-diabetic activities of the extracts from bitter leaves (vernonia amygdalina) and purple fleabane (vernonia cinerea) - Ruth, Alara Oluwaseun (2019)
Diabetes mellitus is a common metabolic disorder, resulting from the inability of a body in responding to the high level of glucose in the bloodstream. The uses of synthetic drugs pose adverse effects on human systems, thus, sourcing alternative from plants is imperative. Therefore, the optimization of microwave-assisted extraction factors in the recoveries of phenolic compounds from bitter leaf (Vernonia amygdalina) and purple fleabane (Vernonia cinerea) leaves as compared with extracts through Soxhlet extraction method had been investigated in this study. The in vitro antioxidant and anti-diabetic activities of the extracts at optimized conditions were as well studied. The effects of MAE factors which include irradiation time, microwave power level, temperature, feed-to-solvent ratio, and ethanol concentration on the extraction yields (% w/w); total phenolic contents, TPC (mg GAE/g d.w.) and total flavonoid contents, TFC (mg QE/g d.w.) were studied using the one-factor-at-a-time (OFAT) experimental method. The two-level factorial design was used to further screen and determine significant extraction factors of MAE. Then, four significant MAE factors namely irradiation time, microwave power, feed-to-solvent ratio, and ethanol concentration were optimized using a face-centered central composite design (FCCCD) of response surface methodology (RSM). Likewise, OFAT was employed to determine the optimal yields through Soxhlet extraction by considering extraction time (1-4 h), feed-to-solvent ratio (1:10-1:25 g/mL) and ethanol concentration (20-80% v/v) as the factors for both plant samples. At the optimized conditions of MAE and Soxhlet extraction, the extracts were characterized using liquid chromatography-mass spectrometry quadrupole time of flight (LC-Q-TOF-MS), Fourier transform infrared spectroscopy (FTIR), and inductively coupled plasma mass spectrometry (ICP-MS). The optimal MAE conditions for V. amygdalina leaves were at irradiation time of 4 min, microwave power level of 558 W; feed/solvent of 1:10 g/mL, and ethanol concentration of 76% v/v. Meanwhile, for V. cinerea leaf, the optimal MAE conditions were at irradiation time of 2 min, microwave power level of 444 W, feed/solvent of 1:14 g/mL, and ethanol concentration of 47% v/v. Moreover, the optimal recoveries of extraction yields, TPC and TFC from V. amygdalina and V. cinerea leaves were obtained using Soxhlet extraction technique at 2 h of extraction time, feed-to-solvent of 1:20 g/mL and ethanol concentration of 60% v/v. The obtained results reflected that MAE can recover higher yields of extracts with the significant quantities of phenolic compounds, antioxidant and anti-diabetic activities from V. amygdalina and V. cinerea leaves as compared with Soxhlet extraction. In addition, LC-Q-TOF-MS analysis confirmed that the identified phenolic compounds through optimized MAE were higher as compared to Soxhlet extraction technique. Moreover, FTIR spectra showing the presence of phenolic compounds were obtained for optimized MAE compared to Soxhlet extraction technique. From the ICP-MS analysis, the presence of mineral elements (potassium, magnesium, calcium, and chromium) in the extracts showed that MAE technique possesses a higher capacity to extract more nutrients compared to Soxhlet extraction. In addition, the extracts from both plant samples showed stronger antioxidant activities whereby the higher quantities were obtained through MAE. The anti-diabetic inhibitory effects were higher than acarbose (a standard drug) for V. amygdalina leaf. However, the anti-diabetic inhibitory effects were closer to that of acarbose for V. cinerea leaves. Thus, the extracts from MAE of V. amygdalina and V. cinerea leaves can be inferred as the promising sources of antioxidants and anti-diabetic medicines for pharmaceutical and functional food industries.